Understanding Interaction and Organizational Issues in Radiology Information Systems: a Qualitative Study with Health Professionals - da Silva, Fábio Aparecido Candido; Pereira, Marluce Rodrigues; Freire, André Pimenta (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context. Interaction with information systems such as PACS and RIS/HIS have been increasingly important in medical practice in hospitals and clinics and are essential for health professionals to perform their activities. Problem. These systems can present usability problems, compromising the efficiency of the process, generating incorrect diagnoses, delays in service and results. Proposal. The aim of this study was to investigate interaction and organizational issues with the use of radiology information systems by health professionals. Theoretical Approach. This qualitative study concerns the work routine of radiology professionals, cognitive learning, interaction and usability problems with systems and other radiology software. Method. The paper presents an exploratory study with thematic analysis of semi-structured interviews with eleven radiology professionals recruited via social networks and e-mails. The interview guide includes the process, responsibilities and factors that interfere in the routine of radiology professionals. Results. Thematic analysis revealed 5 themes that indicate the factors that interfere in the user's routine and in the radiological context, namely: System characteristics affect user usability; Process situations affect user task characteristics; User's behavior in relation to his routine; User experience and knowledge; Users deal with system failures and data loss risks. Contribution and Impact on IS. The results show that the users’ routine and interaction with radiology systems are conditioned to hospital or clinical processes, limiting users. The analysis of this study contributes to highlight usability aspects and business processes that can be improved in (clinical contexts) for a better effectiveness of radiological information systems.